The Analysis of Teachers’ Code Switchings Based on The Perceptions of The Eighth Grade Students of SMP Negeri 2 Sawan - Juliadnyana, I. G.; Suarnajaya, I. W.; Ramendra, D. P. (LPPM Undiksha, 2020)
This research aimed to identify the types of code switching and the students’ perception about code switching used by the English teachers in the eighth grade students of SMP Negeri 2 Sawan. This research was conducted in descriptive qualitative design. The subjects of this research were the eighth grade students and the eighth grade English teachers. The instruments used in this study were observation sheet, questionnaire, and interview guide. The results of this research showed that there were three types of code switching used by the English teachers. The data showed there were (31.7%) of intra sentential code switching, (54.8%) of inter sentential code switching and (13.4%) of inter personal code switching.The results of the questionnaire showed that the average responses of the students were (70.74%), it means that students were catagorized to have positive perception about the use of code switching by the English teachers. The interview shows that the students had positive response about the use of code switching by the English teachers. There were two reasons concerning the students’ positive answer, that is, code switchings that make the students understand the material more easily, and code swicthings that reduce the students’ stress in learning.